Transparency, corruption and ICT (illustrated with Portuguese cases) - Dias, G. P.
With this text we discuss – building from two illustrative Portuguese cases – the role and relevance of Information and Communication Technologies (ICT) in the fight against corruption and in the promotion of better transparency and accountability in government. Starting with a consistent definition of corruption and a distinction between political and administrative corruption, we will consider the opportunities introduced by the development of ICT and its growing usage by government and society. Within the text, we refer to the thirty years’ controversy related to the need and proposed locations for the new Lisbon international airport, analyzing the alleged links between politicians and the construction and real estate industries; and examine the local government, that was the object of more than 40% of the corruption investigations in Portugal in the last four years.